Accumulation of γ‐aminobutyric acid by Enterococcus avium 9184 in scallop solution in a two‐stage fermentation strategy. Issue 4 (22nd July 2015) - Yang, Haoyue; Xing, Ronge; Hu, Linfeng; Liu, Song; Li, Pengcheng
Summary: In this study, a new bacterial strain having a high ability to produce γ‐aminobutyric acid (GABA) was isolated from naturally fermented scallop solution and was identified as E nterococcus avium . To the best of our knowledge, this is the first study to prove that E . avium possesses glutamate decarboxylase activity. The strain was then mutagenized with UV radiation and was designated as E . avium 9184. Scallop solution was used as the culture medium to produce GABA. A two‐stage fermentation strategy was applied to accumulate GABA. In the first stage, cell growth was regulated. Optimum conditions for cell growth were pH, 6.5; temperature, 37°C; and glucose concentration, 10 g·L −1 . This produced a maximum dry cell mass of 2.10 g·L −1 . In the second stage, GABA formation was regulated. GABA concentration reached 3.71 g·L −1 at 96 h pH 6.0, 37°C and initiall ‐monosodium glutamate concentration of 10 g·L −1 . Thus, compared with traditional one‐stage fermentation, the two‐stage fermentation significantly increased GABA accumulation. These results provide preliminary data to produce GABA using E . avium and also provide a new approach to process and utilize shellfish. Abstract : A new strain of Enterococcus avium with high Î³‐aminobutyric acid (GABA)‐producing ability from natural fermented scallop. It is the first time to accumulate GABA by E. avium. Scallop was first used as a culture medium to produce GABA.